Semantic Features and Verb-complements of Directive Verbs: “Ask” and “Request - İşler, Cemre (My University, 2023)
This study investigates semantic and syntactic features of two directive speech act verbs: “ask” and “request”. The research questions guiding the study were: (1) What are the similar and different semantic features of two speech act verbs, ask and request? (2) What are the similar and different syntactic features of two speech act verbs, ask and request? In order to examine these two speech act verbs, both quantitative and qualitative methods were implemented. Data were derived from two main sources: dictionaries and corpus. These were three traditional dictionaries Oxford Advanced Learner’s Dictionary (OALD), the Longman Dictionary of Contemporary English (LDCE) and the American Heritage Dictionary of English (AHDE), and the Corpus of Contemporary American English (COCA). For data analysis, these two directive verbs were confined to declaratives where they were used in the form of explicit performatives (e.g., I ask that). All the sentence patterns that implement explicit performatives were included in the analysis. The attempt was made to find out whether the different semantic and syntactic features can be realized in the use of “ask” and “request”. By focusing its attention on the similarities and differences between the verbs, the study showed the shared meaning and grammatical patterns and the different meanings and patterns that while one fits, the other does not. The findings demonstrated that while both verbs are classified under the same group of categorization as directives, they both exhibit different semantic features and grammatical patterns.
Keywords: Speech acts; COCA; directive verb